Larvicidal activity opposite Aedes aegypti of the essential oil of the dry leaves of Syzygium cumini (L.) Skeels (Myrtaceae) (Research, Society and Development, 2020)
This study aimed to evaluate the larvicidal activity of essential oil (EO) extracted from the dry leaves of Syzygium cumini (L.) Skeels. The hydrodistillation technique was used for EO extraction in a modified Clevenger extractor system. The chemical constituents were obtained by Gas Chromatography coupled to mass spectrometry (GC/MS). For larvicidal activity, Larvae of Aedes aegypti were submitted to OE solutions at concentrations of 10-100 mgL-1,where larvae mortality was evaluated and LC50 was determined. Isocaryofylene was quantified as the majority in THE. The action of the EO was observed as larvicidal where CL50 of 29.58 mg L-1 was determined. The results obtained allowed us to conclude that the studied OE presented efficient larvicidal activity against the larvae of Aedes aegypti, being important and encouraged its use and application.